2017
DOI: 10.1111/cas.13141
|View full text |Cite
|
Sign up to set email alerts
|

CS2164, a novel multi‐target inhibitor against tumor angiogenesis, mitosis and chronic inflammation with anti‐tumor potency

Abstract: Although inhibitors targeting tumor angiogenic pathway have provided improvement for clinical treatment in patients with various solid tumors, the still very limited anti‐cancer efficacy and acquired drug resistance demand new agents that may offer better clinical benefits. In the effort to find a small molecule potentially targeting several key pathways for tumor development, we designed, discovered and evaluated a novel multi‐kinase inhibitor, CS2164. CS2164 inhibited the angiogenesis‐related kinases (VEGFR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…However, the transcription level of p53 did not change, but the protein level increased signi cantly, indicating that Chiauranib might affect the post-transcriptional regulation of p53. It has been reported that Chiauranib could inhibit the phosphorylation of Aurora B, which participated in regulating p53 phosphorylation 8 . Indeed, our results showed that Chiaurinib could inhibit Aurora B phosphorylation in KRAS wild-type CRC cells, thus inducing p53 increasing ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the transcription level of p53 did not change, but the protein level increased signi cantly, indicating that Chiauranib might affect the post-transcriptional regulation of p53. It has been reported that Chiauranib could inhibit the phosphorylation of Aurora B, which participated in regulating p53 phosphorylation 8 . Indeed, our results showed that Chiaurinib could inhibit Aurora B phosphorylation in KRAS wild-type CRC cells, thus inducing p53 increasing ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chiauranib is a novel oral multi-target small molecule inhibitor of select serine threonine-kinases, including the angiogenesis-related kinases (VEGFR1, VEGFR2, VEGFR3, and c-Kit), the chronic in ammation-related kinase CSF-1R, and the mitosis-related kinase Aurora B, with a variety of potential anti-tumor activities [8][9][10] . Chiauranib reduces hepatocellular carcinoma and gastric cancer cell proliferation by simultaneous inhibiting VEGFR2 and Aurora B 8 . Besides, Chiauranib exerts anti-tumor effect against angiogenesis and mitosis in hematologic tumors, such as acute myeloid leukemia and Non-Hodgkin's lymphomas 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study concluded that five multi-targeted compounds (S-258282355, S-258012947, S-259417539, S-258002927, and S-259411474) (Figure 30) with high binding energies that range between −8.7 to −10.3 kcal/mol as well as a good ADMET profile against all three targets be taken into consideration, suggesting them as potential hits for drug development against breast cancer after testing through in vitro and in vivo experiments. Zhou et al (2017) used a computer-aided rational drug design approach that led to the synthesis and characterization of CS2164 (N-(2-aminophenyl)-6-[(7methoxy-4-quinolinyl)oxy]-1-naphthalenecarboxamide, Figure 31) and evaluated as a novel multi-kinase inhibitor through the in vitro studies and the molecular docking.…”
Section: Cancermentioning
confidence: 99%
“…Anlotinib is a multiple RTKI with a broad spectrum of inhibitory action on tumor angiogenesis and growth. CS2164 ( 68 ) is a novel multiple RTKI against tumor angiogenesis . It could suppress the angiogenic RTKs (VEGFR1‐3, PDGFRα, and c‐Kit), mitosis‐related kinase Aurora B, and chronic inflammation related kinase CSF‐1R in a high potency manner with the IC 50 at nanomolar range.…”
Section: Recent Advances In Small‐molecule Antiangiogenic Agentsmentioning
confidence: 99%
“…CS2164 (68) is a novel multiple RTKI against tumor angiogenesis. 173 It could suppress the angiogenic RTKs (VEGFR1-3, PDGFR , and c-Kit), mitosis-related kinase Aurora B, and chronic inflammation related kinase CSF-1R in a high potency manner with the IC 50 at nanomolar range. It is under clinical assessment for the treatment of cancers.…”
Section: Multitarget Rtkis As Antiangiogenic Agentsmentioning
confidence: 99%